3, 4, 5-Trimethoxycinnamin acid ameliorates restraint stress-induced anxiety and depression. (12th January 2015) - Leem, Yea-Hyun; Oh, Seikwan
Highlights: A pharmacological activity of TMCA (trimethoxy cinnamic acid) is measured for anti-stress and anti-depressant. In parallel with behavioral data, long-lasting stimulation of ΔFosB in nucleus accumbens shell subregion was exhibited in response to TMCA. Reduced SC1, the candidate of ΔFosB target gene, mRNA expression in nucleus accumbens of mice administrated by restraint stress was profoundly reversed by TMCA. Collectively, TMCA treatment may be a therapeutic strategy for anxiety and depression. Abstract: The present study investigated whether 3, 4, 5-trimethoxycinnamic acid (TMCA) treatment ameliorated restraint stress-provoked anxiety- and depression-like behaviors in mice. Fourteen consecutive days of restraint stress produced anxiety- and depression-like behaviors, including reduced time and frequency in the open arms of the elevated plus maze (EPM), as well as enhanced immobility times in the forced swim test (FST). However, TMCA (50 mg/kg) treatment ameliorated this effect; mice showed increased time and frequency of visits in the open arms of the EPM and showed reduced immobility in the FST. In parallel with the behavioral data, long-lasting stimulation of ΔFosB in the nucleus accumbens shell subregion was exhibited in response to TMCA. Furthermore, a reduction in expression of SC1, a target of ΔFosB, in the nucleus accumbens of mice subjected to restraint stress was significantly reversed by TMCA (50 mg/kg) treatment. Collectively, these results suggest that TMCA treatment might provide a therapeutic strategy for treatment of anxiety and depression.